Brush‐First ROMP of poly(ethylene oxide) macromonomers of varied length: impact of polymer architecture on thermal behavior and Li+ conductivity. Issue 3 (9th October 2018) - Shibuya, Yoshiki; Tatara, Ryoichi; Jiang, Yivan; Shao‐Horn, Yang; Johnson, Jeremiah A.
ABSTRACT: The properties of polymeric materials are dictated not only by their composition but also by their molecular architecture. Here, by employing brush‐first ring‐opening metathesis polymerization (ROMP), norbornene‐terminated poly(ethylene oxide) (PEO) macromonomers (MM‐n, linear architecture), bottlebrush polymers (Brush‐n, comb architecture), and brush‐arm star polymers (BASP‐n, star architecture), wheren indicates the average degree of polymerization (DP) of PEO, are synthesized. The impact of architecture on the thermal properties and Li + conductivities for this series of PEO architectures is investigated. Notably, in polymers bearing PEO with the highest degree of polymerization, irrespective of differences in architecture and molecular weight (~100‐fold differences), electrolytes with lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) as an Li + source exhibit normalized ionic conductivities ( σ n ) within only 4.9 times difference ( σ n = 29.8 × 10 −5 S cm −1 forMM‐45 and σ n = 6.07 × 10 −5 S cm −1 forBASP‐45 ) at a concentration of Li + r = [Li + ]/[EO] = 1/12 at 50 °C. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2019, 57, 448–455 Abstract : Brush‐first ring‐opening metathesis polymerization (ROMP) provides norbornene‐terminated macromonomers (linear architecture), bottlebrush polymers (comb architecture), and brush‐arm star polymers (BASPs) (star architecture) with varied lengths of poly(ethylene oxide) (PEO) chains. The impact of those distinct PEO architectures on thermal properties and Li + conductivity is investigated. Notably, these polymers with varied architectures are derived from the same components.